Fabrication and characterization of polyvinyl acetate slime phantom for magnetic resonance spectroscopy - Baharudin, Siti Sarah (2020)
The aim of this study is to explore the feasibility, suitability, and compatibility of polyvinyl acetate slime as tissue mimicking phantom for magnetic resonance spectroscopy (MRS) studies. Phantoms are made with gelling agents and some without by measuring the ingredient and mixing them. In this study, there are seven types of phantoms with different ingredient. Four of them are PVA slime phantoms which were fabricated with different additives that are water, oil, milk and salt. While the other three consist of water, oil and milk only which were regarded as control. MRS imaging was performed using Philips Achieva 3 Tesla MRI system available at Department of Radiology, HUSM. All phantoms were characterized base on their MR spectra and chemical shift. The MR spectra and chemical shift of the phantoms were also compared with those of normal and pathological tissue. The result from this study show that the chemical shift and especially the metabolite ratio data are much likely equivalent to human tissue. It can be concluded that PVA slime phantom can be use as tissue mimicking phantom for MRS as the characteristics of the phantom is suitable to use in MRS.